Individual cultural values as determinants of the attitudinal process in the restaurant: a different perspective for understanding brand equity formation - María Eugenia Rodríguez-López; Juan Miguel Alcántara-Pilar; Salvador Del Barrio-García (Tourism & Management Studies)
In an increasingly innovative competitive environment, it is necessary to know the customer in depth and to understand the intrinsic determinants of customer loyalty to the restaurant and brand equity. Culture is a fundamental factor in understanding behaviour, which has often attracted interest because of its moderating rather than determining role. The objective of this research is to examine the determinant role of customers' cultural values (long-term orientation, power distance, and uncertainty avoidance) on the customer's attitudinal process in the restaurant (satisfaction and loyalty) in order to understand how it indirectly affects through the attitudinal process the formation of a restaurant's brand equity. A sample of 540 customers was used, and a SEM model was estimated. The results indicate that cultural values, except for power distance, strongly determine the attitudinal process. Therefore, culture indirectly affects the formation of the restaurant's brand equity.